Precisiones metodológicas que ejecutan los profesores del área de físico matemáticas y su incidencia en el proceso de enseñanza aprendizaje en los estudiantes de octavo, noveno y décimo años del colegio fiscal mixto San Pedro de Vilcabamba. Periodo 2012- 2013. Lineamientos alternativos - Guamán Cabrera, Ángel Gabriel (2014)
This research is provided for in a study of " METHODOLOGICAL RUNNING AREA TEACHERS OF MATHEMATICS PHYSICAL AND ITS IMPACT ON THE TEACHING STUDENTS LEARNING IN EIGHTH , NINTH AND TENTH JOINT FISCAL YEAR COLLEGE SAN PEDRO DE VILCABAMBA . PERIOD 2012-2013. GUIDELINES ALTERNATIVE” Education for its diversity has no definitive answers about the aims, methods and teaching techniques and the implementation, planning and methodological details of teachers, they are insufficient to impart to younger generations an education that is in line with reality current. As a guide the research process raises the following specific objectives: To determine the influence of common methodological considerations teachers running physical area - math, affect the process of learning in students of eighth, ninth and tenth years of Joint Tax College San Pedro De Vilcabamba. Period 2012 - 2013; verify incidence of methodological details used by Teachers physical area - mathematics in the teaching-learning process among students in eighth, ninth and tenth years of the Joint Tax College San Pedro de Vilcabamba. Period 2012 - 2013, develop guidelines aimed at renovating alternative methodological precisions Physical area - Mathematics, to enhance the teaching – learning process. As a result of research work the following results are determined, they are presented in statistical tables and charts, according to the first variable: methodological precisions teachers running Physical area - Math, is observed that teachers in their full use of the curriculum texts as they are easier to understand and apply, thus inferring that the majority use word classes can generate very tedious and uninteresting for students. And also in most classes teachers do not apply creativity, deducing that do not use various teaching materials available today, as they are of vital importance for the study and thus implement the various concepts, theories and methodologies developed for teaching geared to meet the knowledge and student learning. In the same way according to the second variable : The impact on the process of teaching - learning emphasizes the application of the technique of the work directed ( task submission and review extraclase) , which can be determined since some rebuttal according to information obtained by the teacher is always performed , while on the other hand the information obtained by students that this activity is observed it is not often performed , being an activity that should be performed periodically since it determines the weaknesses students have the time to put into practice the knowledge gained and put it against the possible solutions to the problems presented.